Clines Without Classes: How to Make Sense of Human Variation. (September 2014) - Fujimura, Joan H.; Bolnick, Deborah A.; Rajagopalan, Ramya; Kaufman, Jay S.; Lewontin, Richard C.; Duster, Troy; Ossorio, Pilar; Marks, Jonathan
This article examines Shiao, Bode, Beyer, and Selvig's (2012) arguments in their article "The Genomic Challenge to the Social Construction of Race" and finds that their claims are based on fundamentally flawed interpretations of current genetic research. We discuss current genomic and genetic knowledge about human biological variation to demonstrate why and how Shiao et al.'s recommendations for future sociological studies and social policy, based on their inadequate understanding of genomic methods and evidence, are similarly flawed and will lead sociology astray.